Applicability analysis of high-speed railway system under the action of near-fault ground motion. Issue 139 (December 2020) - Jiang, Lizhong; Yu, Jian; Zhou, Wangbao; Yan, Wangji; Lai, Zhipeng; Feng, Yulin
Abstract: Studying the applicability of existing bridge and track systems of high-speed railway in near-fault areas is crucial and urgent, because the current seismic design methods seldom consider the characteristics of the near-fault ground motion. By comprehensively considering the uncertainties in ground motion and structural parameters, a large-sample analysis method for near-faults area was proposed. In addition, an integrated finite element model for beam bridge-track system of high-speed railway was used to calculate the seismic response of the structure under the action of near-fault ground motion. The over-limit state and applicability of seismic response of key components and systems were predicted and evaluated. The analysis results indicate that the statistical characteristics of structural seismic response and over-limit state tend to be stable with increasing number of samples. Under the near-fault ground motion: (i) the piers of high-speed railway are hard to yield (ii) bearings are damaged severely, and (iii) the piers have insufficient shear capacity and the characteristics of structural seismic damage are not in accordance with the concept of ductility design. The sliding layer of the track structure is severely damaged by the transverse and longitudinal ground motions, while the CA mortar layer and fastener are mainly damaged by the transverse ground motion. The applicability of bearings, the anti-shearing behavior of piers, and the inter-layer structure of tracks make it difficult to achieve the goal of the near-fault fortification against ground motion. Highlights: The current seismic design methods seldom consider the characteristics of the near-fault ground motion. A structural analysis method that fully considers the effects of near fault ground motion is proposed in this paper. This method can reasonably predict and evaluate over-limit state and applicability of the structures.